Epidemiological profiling of SARS-CoV-2 with focus on one-health approaches in mitigating COVID-19 pandemic - TAMTA, SHIKA; VINODHKUMAR, O R; KARTHIKEYAN, A; DUBAL, Z B; KHAN, SHARUN; A SAIED, ABDUL RAHMAN; DHAWAN, MANISH; DHAMA, KULDEEP; MALIK, Y S (The Indian Journal of Animal Sciences, 2021)
Of the 1,415 human pathogens identified, 175 are responsible for causing emerging diseases, 132 are zoonotic and majority of the diseases are categorized as emerging or re-emerging. Emerging novel Coronavirus (COVID- 19) is one of them, and it is responsible for causing social and economically critical disease in both humans and animals. This review presents the understanding of epidemiological characteristics of the COVID-19 pandemic related to host, agent, and the environment with transmission and spread of the disease for better prevention of the COVID-19. The inclination of the viruses to spillover between different species and determining the number of the reservoir of coronaviruses in an entirely new host to create infection is of emerging importance. The understanding of disease patterns will potentiate our expertise to alert how, when, and where the potential epidemic will occur. One health approach involves co-operation from all the sectors, including healthcare (medical and veterinary), environmental, pharmaceutical, educational, research, police, and administration, to combat the COVID-19 pandemic and reduce the public health threat.